2020
DOI: 10.1007/s10346-020-01506-3
|View full text |Cite
|
Sign up to set email alerts
|

Landslides after wildfire: initiation, magnitude, and mobility

Abstract: In the semiarid Southwestern USA, wildfires are commonly followed by runoff-generated debris flows because wildfires remove vegetation and ground cover, which reduces soil infiltration capacity and increases soil erodibility. At a study site in Southern California, we initially observed runoff-generated debris flows in the first year following fire. However, at the same site three years after the fire, the mass-wasting response to a long-duration rainstorm with high rainfall intensity peaks was shallow landsli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 68 publications
(81 reference statements)
4
112
0
4
Order By: Relevance
“…This corresponds to the evidence from the bootstrap analysis suggesting that dried out soil or slow vegetation regrowth may be an important part of the post-wildfire landslide mechanism in this region. Vegetation regrowth as a main control of landslide susceptibility is supported by a study of landslide occurrence in the San Gabriel mountains of the US by Rengers et al (2020), in which the authors found that hillslopes with slower vegetation regrowth were more likely to have landslides.…”
Section: Discussionmentioning
confidence: 91%
“…This corresponds to the evidence from the bootstrap analysis suggesting that dried out soil or slow vegetation regrowth may be an important part of the post-wildfire landslide mechanism in this region. Vegetation regrowth as a main control of landslide susceptibility is supported by a study of landslide occurrence in the San Gabriel mountains of the US by Rengers et al (2020), in which the authors found that hillslopes with slower vegetation regrowth were more likely to have landslides.…”
Section: Discussionmentioning
confidence: 91%
“…Root strength is generally hypothesized to be at a minimum at some intermediate time period following disturbance, once the roots of dead vegetation have decayed and before roots of new growth are well established (Rice, 1982;Schmidt et al, 2001). Rengers et al (2020), for example, documented a landslide density of 11.8 landslides/km 2 due to a rainstorm that impacted the 2016 San Gabriel Complex burn scar after 3 years of recovery compared with densities of 0.2 landslides/km 2 in a nearby unburned area and 0.8 landslides/km 2 in a nearby burn scar that had been recovering for 5 years. Root strength at our study area may not have been that different in the burned and unburned areas given that the rainstorm occurred less than 3 months after the fire was contained, leaving little time for roots to decay.…”
Section: Discussionmentioning
confidence: 99%
“…Landslide hazard is increasing year by year due to more intense and frequent rainfall as a consequence of climate change [1]. Additionally, secondary causes such as wildfires play an important role in promoting landslides [2]. The poorest residents are often the most vulnerable to landslides because in many cases they live in the most dangerous areas [3][4][5][6].…”
Section: Project Overview Inform@risk 1project Background and Goalsmentioning
confidence: 99%